2022
DOI: 10.1093/brain/awac376
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape across 474 surgically accessible epileptogenic human brain lesions

Abstract: Understanding the exact molecular mechanisms involved in the etiology of epileptogenic pathologies with or without tumor activity is essential for improving treatment of drug-resistant focal epilepsy. Here, we characterize the landscape of somatic genetic variants in resected brain specimens from 474 individuals with drug-resistant focal epilepsy using deep whole-exome sequencing (>350×) and whole-genome genotyping. Across the exome, we observe a greater number of somatic single-nucleotide variants (SNV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 99 publications
1
45
0
Order By: Relevance
“…One-hundred-thirty pre-selected samples of LEAT with uncharacteristic histopathology and clinical features were collected at the University Hospital in Erlangen, Germany; Klinikum Bethel-Mara, Bielefeld University, Germany; and Schoen-Klinik Vogtareuth, Germany. Seventy-two samples were snap frozen at -80°C and submitted to whole-exome sequencing and Single-Nucleotide-Polymorphism analysis (SNP) with Global Screening Array Microarrays v1.0 (Illumina, San Diego, CA, USA) as described elsewhere (Lopez-Rivera et al, 2022). Eighty-six samples were formalin-fixed and paraffin-embedded (FFPE) and submitted to DNA methylation analysis using 450K and 850K/EPIC arrays (Illumina, California, USA).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One-hundred-thirty pre-selected samples of LEAT with uncharacteristic histopathology and clinical features were collected at the University Hospital in Erlangen, Germany; Klinikum Bethel-Mara, Bielefeld University, Germany; and Schoen-Klinik Vogtareuth, Germany. Seventy-two samples were snap frozen at -80°C and submitted to whole-exome sequencing and Single-Nucleotide-Polymorphism analysis (SNP) with Global Screening Array Microarrays v1.0 (Illumina, San Diego, CA, USA) as described elsewhere (Lopez-Rivera et al, 2022). Eighty-six samples were formalin-fixed and paraffin-embedded (FFPE) and submitted to DNA methylation analysis using 450K and 850K/EPIC arrays (Illumina, California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Following routine DNA extraction from the frozen tissue samples, whole-exome sequencing (WES) was performed at a coverage of >350x using Agilent SureSelect Human All Exon V7 enrichment and paired-end reads (151bp) Illumina sequencing. Paired-end FASTQ files were pre-processed following GATK best practices (DePristo et al, 2011) and genetic variants were identified as described previously (Lopez-Rivera et al, 2022). These samples were also genotyped using the Global Screening Array with Multi-disease drop-in (GSA-MD v1.0; Illumina, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations